(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Any modern economy’s lifeline is the banking industry. It is one of the crucial financial pillars of the financial system, and its impact on an economy’s success or failure is crucial. A bank is a business that deals in money and credit and wants to make money. It is a financial institution that deals in money because it takes deposits from the public and keeps them safe in its custody. Additionally, it offers credit. The primary objective of this research is to determine whether public sector banks, particularly State Bank of Hyderabad and Andhra Bank, have adhered to the Narasimham Committee’s recommendations and whether their performance lives up to those expectations.